Pregled ugotovitev zaključnih del študentk in študentov Fakultete za socialno delo o socialnem delu z ljudmi z demenco - Rihter, Liljana (Socialno delo, 2022)
A meta-analysis of students' theses from the past five years (2016–2020) on the topic of social work with people with dementia is presented. Among the themes explored, work in institutions as well as work in the family setting of people with dementia predominate; community work topics emerge to a lesser extent. Thus, the role of social work and the use of social work methods are researched somewhat more in institutions, but again, only in individual institutions. However, this topic does not appear in research on people with dementia in the home setting. Most research is qualitative and based on non-random convenience samples using interviews as the method of data collection. Often, students explore the challenges and needs of those involved in caring for people with dementia, but with less emphasis on numbers. In the future, the focus will need to be on research on community and on (social) work with people with dementia in their home environments, and the use of social work methods and other forms of work with people with dementia need to be explored in more depth.
Keywords: dolgotrajna oskrba; institucionalizacija; institutionalisation; long-term care; methods of work; metode dela; old people; raziskovanje; research; stari ljudje